Decline of Male Labor Market Participation: The Role of Declining Market Opportunities - Juhn, C. (Quarterly Journal of Economics, 1992)
This paper uses micro data from the Current Population Surveys to document the secular decline in labor market activity among prime age men from 1967 to 1987. Declines in employment occur at all ages but are found to be particularly severe among less-educated and low-wage men. Information on the cross-section wage-employment relationship and on actual wage changes indicates that the initial fall in employment from the late 1960s to the early 1970s is entirely attributable to falling labor supply whereas since the early 1970s, wage changes predict most of the decline in employment for whites and approximately half of the decline for blacks.